fo005544: Maurice Dequeecker - Volksgazet
"Zwartwit-foto van Maurice Dequeecker, 1 december 1964. 1ste rij v.l.n.r. Dequeecker Maurice, Craeybeckx Lode, gouverneur Declerck (?). FULL TEXT AVAILABLE AT AMSAB-ISH"